Analisis Peran dan Dampak Perkembangan Teknologi Digital terhadap Pembentukan Perilaku Konsumtif Generasi Z - Rahadian Faisal Hakim; Selpi Selpi; Najma Najdain; Roska Jemima Sirait; Faruq Fadhillah Alawi; Rina Rahmayati; Putri Nuraeni Rahma (Prosiding Seminar Nasional Ilmu Pendidikan, 2026)
The rapid development of digital technology has significantly transformed consumption patterns in modern society, particularly among Generation Z, who have grown up alongside the internet and social media. This study aims to analyze the role of digital technology in shaping the consumptive behavior of Generation Z and to identify the factors influencing such behavior. The research employed a qualitative approach using a literature review method by examining various journals, scientific articles, and relevant academic sources. The findings indicate that social media, influencers, e-commerce platforms, and digital payment systems such as e-wallets and paylater services significantly contribute to increased consumptive and impulsive buying behavior among Generation Z. In addition, the Fear of Missing Out (FOMO) phenomenon, digital trends, and low financial literacy further strengthen excessive consumption tendencies. The convenience of digital transactions and continuous exposure to online promotions have shifted consumption priorities from needs to desires. Therefore, improving financial literacy and selfcontrol is essential to help Generation Z respond more wisely to the rapid advancement of digital technology.